Reviewing systematic literature reviews: ten key questions and criteria for reviewers - Andreas Kuckertz; Joern Block (Management Review Quarterly, 2021)
Systematic literature review articles are important for synthesizing knowledge in management and business research. However, to date, we lack clear guidelines how to review such articles. This editorial takes the perspective of the reviewer. It presents ten key questions and criteria that reviewers should ask when reviewing systematic literature reviews.
Keywords: 650; L20; L21; L22